2022
DOI: 10.3389/fimmu.2022.1050183
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis-disease modifying therapies affect humoral and T-cell response to mRNA COVID-19 vaccine

Abstract: BackgroundThe mRNA vaccines help protect from COVID-19 severity, however multiple sclerosis (MS) disease modifying therapies (DMTs) might affect the development of humoral and T-cell specific response to vaccination.MethodsThe aim of the study was to evaluate humoral and specific T-cell response, as well as B-cell activation and survival factors, in people with MS (pwMS) under DMTs before (T0) and after two months (T1) from the third dose of vaccine, comparing the obtained findings to healthy donors (HD). All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
(92 reference statements)
1
6
0
Order By: Relevance
“…In our setting, an uneven T-cell subset distribution was observed, in which IFNγ-IL2-TNFα+ and IFNγ-IL2+TNFα--producing T-cells prevailed. Since the quality of T-cell response, characterized by a multifunctional profile, has been associated with higher protection in response to infections and vaccinations [ 6 , 7 , 8 , 36 , 37 ], the highly uneven subset distribution of T-cells found in our cohort might indicate a qualitatively inferior T-cell response to vaccination. However, after twelve months since the third dose of the SARS-CoV-2 mRNA-based vaccine, a dynamic change in the subset distribution was observed, in which a more heterogeneous distribution, like HD ones, was observed in SOT-Rs as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our setting, an uneven T-cell subset distribution was observed, in which IFNγ-IL2-TNFα+ and IFNγ-IL2+TNFα--producing T-cells prevailed. Since the quality of T-cell response, characterized by a multifunctional profile, has been associated with higher protection in response to infections and vaccinations [ 6 , 7 , 8 , 36 , 37 ], the highly uneven subset distribution of T-cells found in our cohort might indicate a qualitatively inferior T-cell response to vaccination. However, after twelve months since the third dose of the SARS-CoV-2 mRNA-based vaccine, a dynamic change in the subset distribution was observed, in which a more heterogeneous distribution, like HD ones, was observed in SOT-Rs as well.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell-specific response was assessed using a multiparametric flow cytometry after overnight stimulation, as previously described [ 8 , 27 ]. Moreover, to assess the Omicron variant T-cell response, PepTivator SARS-CoV-2 Prot_S B.1.1.529/BA.5 Mutation Pool (Milteny Biotec, Bergisch Gladbach, Germany) that covers selectively mutated regions was used to supplement PepTivators covering the sequence of the wild type of spike glycoprotein (“S”) in order to detect immune responses towards all three variants: Wuhan (wild type), B.1.1.529/BA.4, and B.1.1.529/BA.5 variant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, B cells are involved in the response to infections [ 48 , 49 ] and vaccination [ 50 , 51 ]. Thus, in the present study, the B cell activation markers BAFF, APRIL and CD40L were analyzed longitudinally in pwMS treated with ocrelizumab, correlating these findings to the occurrence of infectious events.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, for other diseases, such as influenza, immunosuppression is known to attenuate the vaccine response [ 19 ]. Along these lines, first publications in patients under immunosuppressive therapy have already shown that, depending on the disease and the medication, the immune response to SARS-CoV-2 infection detected by PCR and COVID-19 vaccination may be severely attenuated or even absent [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%